Influência de materiais de proteção superficial na resistividade elétrica e absorção capilar do concreto - Santor, Marcelo Silva (2011)
The durability of concrete structures is the result of protective action of concrete over the rebar. When the passivation of steel ceases to exist the structure becomes vulnerable to the phenomenon of corrosion, which spread after start is largely controlled by the electrical resistivity of concrete. Another important factor in the durability of concrete structures is the absorption, which is one of the properties governing the transport of ions inside the concrete. This study aimed to evaluate the electrical resistivity and capillary absorption of concrete that have undergone surface treatment: a monolithic polymeric mortar applied in a layer of 4mm, and a pore blocker with a single coat and a pore blocker with a double coat. The concrete surface subjected to treatment were made with three types of cement,CP IV-32, CP II-F 32 and CP V and levels of compressive strength of 15MPa, 20MPa and 25MPa. The electrical resistivity was measured by the method of four electrodes and capillary absorption by the method NBR 9779. Treatment with the pore blocker with a double coat was more effective in reducing capillary absorption than a pore blocker with a single coat for the three types of cement, but the best results were obtained using the polymer mortar. In this work the pozzolanic effect present on cement CP IV became more clear in the result of electrical resistivity for all treatment studied. The different behavior of the electrical resistivity of concrete with cement CP IV in relation to others, CPII F and CP V, is justified by changes in the microstructure of the paste, pore refinement and composition of pore solution. In addition to this, when compared to concrete made with CP V, the lower relations/binder of CP IV to obtain the compressive strengh levels investigated, fck = 15 Mpa , 20Mpa and 25Mpa. Even the reference concrete without surface treatment showed values of resistivity well above the actual reference compounds with CP II-F and CP V and also subjected to surface treatment.